Wear behavior of additively manufactured 316L/SiCp composites with up to 60 wt% SiCp. Issue 22 (15th November 2022) - Sánchez de Rojas Candela, C.; Riquelme, A.; Rodrigo, P.; Torres, B.; Rams, J.
Abstract: The wear behavior of 316L composites reinforced with up to 60% SiCp additively manufactured by Laser-Directed Energy Deposition (DED) has been studied and the effect of adding different percentages of SiC particles (SiCp) has been evaluated and compared with 316L stainless steel. The wear tests were carried out on the pin-on-disc configuration. The microstructure and microhardness of the samples have been studied, and the friction coefficient, pin and disc mass loss, and wear rate have been correlated with them. The worn surfaces and the corresponding debris were observed under a scanning electron microscope (SEM) and 3D optic profilometer so that the wear mechanisms have been determined. Increasing the SiCp content results in a better wear performance in which the composite mass loss reduces while the disc mass loss increases. Composite with 40 wt% SiCp shows hardness that is five-fold that of the 316L and a ten-fold wear resistance. For 60 wt% SiC content, the presence of graphite also reduced the friction coefficient. The incorporation of SiCp changes the wear mechanisms from adhesive for unreinforced 316L to delamination, abrasive, and oxidative for reinforced composites. Highlights: Wear behavior of highly reinforced 316L/SiCp has been studied. Increasing the reinforcement rate reduces the wear of the composites. 40 wt% SiCp shows x5 hardness and x10 wear resistance than 316L. For 60% SiCp graphite precipitates have a lubricant effect. Increasing reinforcement in 316L increments the oxidative and delamination mechanisms.